Thermal comfort and energy consumption analysis for engineering laboratory building in UTeM - Manaf, Fakhir Hussain (2017)
This study aims to conduct the1mal comfort and energy consumption analysis at Mechanical Engineering Laboratories Complex (KMKM). A few laboratories have been selected as the case study for sample measurement with an air-conditioning system and without air conditioning system. Measurement of thermal comfort level in student laboratories is accomplished by using thermal microclimate and indoor air quality meter. In addition, the Building Energy Index (BEl) was also being determined for each block of the building. Based on the calculation, the overall BEl from March 2015 to February 2016 is 86.5634 kWh/m2/year. Meanwhile, the BEl for March 2016 to February 2017 is 73.456 kWh/m2/year. The calculation shows that the KMKM building energy index for (March 2015 to February 20 16) and (March 2016 to February 201 7) is lower than the maximum range of the Malaysia Standard 1525:2014. The measurement data is then compared with the current Malaysia Standard 1525:2014 and ASHRAE:-55 Standard. The results of this study shows that overall average air velocity is 0.116 m/s, less than Malaysian Standard 1525:2014. The overall average operative temperature is 25.88°C, the overall average relative humidity is 60.15% and the overall average C02 is 511.28 ppm were within the range of Malaysian Standard 1525:2014.